Post- Impact Fatigue Damage Analysis of Quasi Isotropic CFRP Laminates through Infrared Thermography - Raghu Vasu Prakash; Mathew John (Fracture and Structural Integrity)
Carbon fiber reinforced plastic (CFRP) materials used for lightweight aircraft structures are susceptible to low velocity accidental impacts during manufacture and while in service. In this study the CFRP laminates subjected to low velocity impact conditions of three different energy levels were tested under various fatigue loading conditions till it reached the failure state. The infrared thermography NDT technique was used for the damage analysis of these post-impact fatigue loaded CFRP specimens to understand the damage distribution across the specimen. The cooling response curves obtained from the active thermography of the post impact fatigue specimens under four different combinations (transmission or reflection mode with impacted or un-impacted surface facing camera) for each of the specimens were analyzed. The rate of cooling in the temperature response curves is different for each specimens subjected with various post impact-fatigue loading conditions and it seems to be correlated with the extent of post-impact fatigue damage present in each specimen quantified through X-ray CT image processing. The temperature rise observed in the passive thermography at the fiber/ply breakage during static strength tests were proportional to corresponding load drops and the non-homogeneous spread of damage at the onset of tensile failure was seen from the thermographs.